2008
DOI: 10.1128/jb.00452-08
|View full text |Cite
|
Sign up to set email alerts
|

Bias between the Left and Right Inverted Repeats during IS911Targeted Insertion

Abstract: IS911 is a bacterial insertion sequence composed of two consecutive overlapping open reading frames (ORFs [orfA and orfB]) encoding the transposase (OrfAB) as well as a regulatory protein (OrfA). These ORFs are bordered by terminal left and right inverted repeats (IRL and IRR, respectively) with several differences in nucleotide sequence. IS911 transposition is asymmetric: each end is cleaved on one strand to generate a free 3-OH, which is then used as the nucleophile in attacking the opposite insertion sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…On the basis of these data, we hypothesize that IS256 transposase-mediated strand processing occurs preferentially, albeit not exclusively, at the left-hand terminus, which then triggers the reactions leading to the circularization of the element. Asymmetric transposase activity has also been reported for other circle-forming elements, such as IS30 and IS911, and may occur at different stages of the transposition pathway (41,44). Differential transposase activities at specific flanking or target sequences may involve a range of factors and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these data, we hypothesize that IS256 transposase-mediated strand processing occurs preferentially, albeit not exclusively, at the left-hand terminus, which then triggers the reactions leading to the circularization of the element. Asymmetric transposase activity has also been reported for other circle-forming elements, such as IS30 and IS911, and may occur at different stages of the transposition pathway (41,44). Differential transposase activities at specific flanking or target sequences may involve a range of factors and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, specific host factors, such as IHF, or the DNAmethylation status were found to play a role in some elements (i.e., IS10 and IS50) (46,50). Also, differential binding affinities of the enzyme to the transposon ends or subterminal sequences adjacent to the IRs can have an impact on the process (e.g., in IS911 and IS30) (41,44). Clearly, more studies are required to answer the question of how the "biased" transposase reaction in IS256 is mediated at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that transposase-mediated circularization of IS 256 preferentially starts with a sequence-specific first-strand cleavage at the left IS terminus ( Hennig and Ziebuhr 2010 ). Similarly, the asymmetric transposition of IS 911 was shown to be a result of differential recognition of IRr and IRl by the transposase ( Rousseau et al 2008 ). Based on the analysis of the orientation of insertion of the different TEs that target promoter regions, we propose that the asymmetric recognition of the two IRs is responsible for the specific orientation of most TEs encoding p-MULT 3 transposases with the IRr next to the targeted promoter sequence.…”
Section: Discussionmentioning
confidence: 99%
“…SCB nt , which is involved in the normal transposition insertion pathway is thought to differ from both SCA and SCB t and to include the second IS911 protein, OrfA. This second transposition protein binds nonspecifically to DNA and also interacts with OrfAB (see Transposition proteins: DNA sequence recognition, multimerization and catalytic domains section above) (18,36), is proposed to direct an OrfAB-junction complex, the product of the replicative IS911 excision (see below), to a randomly chosen target DNA to form SCB nt (68,69). This is based on the observation that integration of the transposon circle intermediate is greatly stimulated by preincubation of OrfAB and OrfA in an in vitro reaction (70).…”
Section: Insertion Synaptic Complex Scbmentioning
confidence: 99%